1996
DOI: 10.1074/jbc.271.31.18456
|View full text |Cite
|
Sign up to set email alerts
|

Undersulfation of Proteoglycans Synthesized by Chondrocytes from a Patient with Achondrogenesis Type 1B Homozygous for an L483P Substitution in the Diastrophic Dysplasia Sulfate Transporter

Abstract: ). To ascertain the consequences of the sulfate transport defect on proteoglycan synthesis, we studied the structure and sulfation of proteoglycans in cartilage tissue and in fibroblast and chondrocyte cultures from a fetus with achondrogenesis 1B. Proteoglycans extracted from epiphyseal cartilage and separated on agarose gels migrated more slowly than controls and stained poorly with alcian blue. The patient's cultured cells showed reduced incorporation of [ S]sulfate relative to [3 H]glucosamine, impaired up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 35 publications
1
59
0
1
Order By: Relevance
“…In branchial arches (white arrows) and AER of limb buds (black arrowheads) in C4st1 mutant (gt/gt) embryos, a C4st1 exon I-specific signal (E) is present, but an exon II/III-specific signal (F) is absent. (Hronowski and Anastassiades, 1988;Ippolito et al, 1983), and it has also been reported that undersulfation of proteoglycans leads to reduced Alcian Blue staining (Rossi et al, 1996); thus, the reduction in Alcian Blue staining probably reflects a reduction in GAG content and C4S levels in the cartilage growth plate. Closer inspection of mutant skeletons revealed reduced bone length, but increased width in long bones as well as the iliac bone ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In branchial arches (white arrows) and AER of limb buds (black arrowheads) in C4st1 mutant (gt/gt) embryos, a C4st1 exon I-specific signal (E) is present, but an exon II/III-specific signal (F) is absent. (Hronowski and Anastassiades, 1988;Ippolito et al, 1983), and it has also been reported that undersulfation of proteoglycans leads to reduced Alcian Blue staining (Rossi et al, 1996); thus, the reduction in Alcian Blue staining probably reflects a reduction in GAG content and C4S levels in the cartilage growth plate. Closer inspection of mutant skeletons revealed reduced bone length, but increased width in long bones as well as the iliac bone ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Once significant lumen has formed, Ci-Slc26aα may then shuttle sulfate into the cytoplasm, providing the substrate for the sulfation of luminal glycoaminoglycans that will facilitate further lumen expansion. It has been reported that the proteoglycans synthesized by chondrocytes from a patient with achondrogenesis type 1B homozygous for an L483P substitution in SLC26A2 were severly undersulfated (26). Ci-Slc26aα L485P, which is unable to transport sulfate, fails to support lumen expansion, validating the importance of the structural element at and around this residue in maintaining the protein function in vivo.…”
Section: Transport Activity Of Ci-slc26aα Is Essential For Its In Vivmentioning
confidence: 99%
“…4B). Ci-Slc26aα L485P, which corresponds to the L483P mutation in SLC26A2 from patients with achondrogenesis type 1B (26), also failed to rescue the lumen formation defect (Fig. 4D).…”
Section: Transport Activity Of Ci-slc26aα Is Essential For Its In Vivmentioning
confidence: 99%
“…Taken together, these results suggested that chondrocytes evidently possess the DTDST sulfate/chloride antiport system. deficient Culture-Undersulfation of proteoglycans is a major consequence of impairment of the DTDST transport system in chondrocytes (7). Thus, we studied the growth factor response of chondrocytes associated with undersulfated proteoglycans.…”
Section: Structure Of Rat Dtdst Gene and Tissue Distribution Of Itsmentioning
confidence: 99%